Assessment of alternative simulation techniques in nonlinear time history analyses of multi-story frame buildings: A case study. Issue 98 (July 2017) - Karimzadeh, Shaghayegh; Askan, Aysegul; Yakut, Ahmet; Ameri, Gabriele
Abstract: In regions with sparse ground motion data, simulations provide alternative acceleration time series for evaluation of the dynamic response of a structure. Different ground motion simulation methods provide varying levels of goodness of fit between observed and synthetic data. Before using the seismologically acceptable synthetic records for engineering purposes, it is critical to investigate the efficiency of synthetics in predicting observed seismic responses of structures. For this purpose, in this study we present nonlinear time history analyses of multi-story reinforced concrete frames under observed and synthetic records of a particular earthquake. Synthetic records of 6 April 2009 L′Aquila (Italy) earthquake (Mw=6.3) are simulated using both the Hybrid Integral-Composite method and the Stochastic Finite-Fault method. Results of analyses from observed and the alternative synthetic records of this event are compared in terms of maximum displacement, acceleration and plastic beam rotation of each story level. Our results indicate that the match between the Fourier Amplitude Spectrum of the observed and synthetic records around the frequencies that correspond to the fundamental period of the structure (mainly within 0.2–1.2% of the fundamental period) governs the misfit between the observed and synthetic nonlinear responses. It is also shown that even for cases where nonlinear behavior is more likely, period-dependent SDOF indicators of goodness of fit between a particular observed and corresponding synthetic records represents the difference in MDOF behavior of frame structures due to these records. Finally, simulation of realistic amplitudes over the entire broadband frequency range of interest is found to be critical while using the synthetics for earthquake engineering purposes. Highlights: Two alternative simulation methods are evaluated in terms of structural responses. One stochastic and one hybrid simulation method is tested on three frame structures. The misfits around the fundamental period determine the accuracy of the response. For this case study, seismologically acceptable synthetics yield close responses.